THE PERCEPTION OF ANGLICAN DIOCESE OF EGBU ON HERBAL MEDICINE IN RELATION TO PENTATEUCHAL THEOLOGY OF ‘ESE - ABILAWON OLUWASEUN FUNMI (International Studies Journal)
In spite of the fact that the Bible does not condemn herbal medicine, there are different perceptions and understanding among people. Some people perceive herbal medicine to be evil, fetish and views the herbal practitioners as idol worshippers, while others accept the use of herbs. Some Christian organizations and Churches condemn the use of herbal medicine, derogating it to be Satanic. These controversies that trail herbal medicine has become an issue to be investigated, in light of Pentateuchal Theology of 'eseb' (herb). This study will therefore, examine the perception of the Diocese of Egbu in Imo State Nigeria, on the use of herbal medicine. This study used basically sociological research method and exegesis which involved the use of books, journals, articles, periodicals, oral interviews, questionnaire, and internet resources relevant to the study. This study was able to find out that the book of Genesis which is the book of all beginnings gave an account on how herbs ('eseb') came into existence through the work of God creation on the third day by sprouting forth from the earth. On the sixth day after man was created God instructed man that herbs will serve as meat for him and to the animal kingdom. Herbs is not in any way connected to Satan, neither is it evil nor fetish, but God the Creator in Genesis 1:12, saw that herbs was good and would be of great benefit to man and animals. Herbs ('eseb') according to Genesis 1:11-12, 29-30; came into existence through the spoken word of God. This depicts how much love God has for humanity and his ability to provide and supply man's need even before creating man. Therefore, herbal medicine is a gift of God to mankind which should be appreciated and respected as it contributes to longevity and add nutritional value to human diet. The researcher therefore recommends that seminars and conferences be held to educate both Christians leaders and Christians on the subject matter of herbal medicine. Professionals in the field of herbs should be encouraged by government policy for them to carry out research on some of the curative herbs that are found in our localities in other to authenticate their potency.